2016
DOI: 10.1177/2050640616630117
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis: Small intestinal bacterial overgrowth in chronic pancreatitis

Abstract: Background: Evidence on small intestinal bacterial overgrowth (SIBO) in patients with chronic pancreatitis (CP) is conflicting. Aim: The purpose of this study was to perform a systematic review and meta-analysis on the prevalence of SIBO in CP and to examine the relationship of SIBO with symptoms and nutritional status. Methods: Case-control and cross-sectional studies investigating SIBO in CP patients were analysed. The prevalence of positive tests was pooled across studies, and the rate of positivity between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 33 publications
1
59
1
6
Order By: Relevance
“…45, 46 SIBO can exacerbate pancreatic exocrine insufficiency (PEI) suggesting that treatment of SIBO would help patients with PEI. 47 In a meta-analyses by Capurso et al, the mean prevalence of SIBO in patients with chronic pancreatitis was reported to be 36% (95%CI 17–60%), 48 although significant heterogeneity between studies was noted. In a subsequent study, Jandhayala et al examined 16 patients with chronic pancreatitis, 14 with chronic pancreatitis with diabetes and 10 healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…45, 46 SIBO can exacerbate pancreatic exocrine insufficiency (PEI) suggesting that treatment of SIBO would help patients with PEI. 47 In a meta-analyses by Capurso et al, the mean prevalence of SIBO in patients with chronic pancreatitis was reported to be 36% (95%CI 17–60%), 48 although significant heterogeneity between studies was noted. In a subsequent study, Jandhayala et al examined 16 patients with chronic pancreatitis, 14 with chronic pancreatitis with diabetes and 10 healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with burping, flatulence, dyspepsia, and other symptoms related to food intake, SIBO should be considered, especially in patients after pancreatic surgery or antibiotic therapy or in those with DM [46]. …”
Section: Small Bowel Bacterial Overgrowthmentioning
confidence: 99%
“…В 2016 г. опубликованы результаты метаанализа, в который вошли 9 рандомизированных исследова ний (336 больных ХП) [25]. Отбирались исследова ния, в которых СИБР диагностировали с помощью водородных дыхательных тестов (с глюкозой, га лактозой, сахарозой или ксилозой) и/или бактерио логического исследования аспирата из тонкой киш ки.…”
Section: огляди / обзорыunclassified